Tinjauan Yuridis Kekuatan Eksekutorial Objek Jaminan Fidusia bagi Debitur yang Melakukan Cidera Janji - Akar Yoga Elsisi Suanti, Elvana; Permata Sari, Ayu; Martia, Vivi; Nur Hasanah, Vidiawati (UNIVERSITAS SERAMBI MEKKAH, 2024)
In the effort to foster social justice in the era of globalization, the Indonesian government has been reforming economic regulations to align policies with Pancasila ideology and the 1945 Constitution, including in the financing sector. This study examines the implementation of fiduciary guarantee executions, previously governed by Law No. 42 of 1999, and the significant changes following Constitutional Court Decision No. 18/PUU-XVII/2019. The research employs a descriptive-analytical method, involving an in-depth analysis of primary and secondary legal materials to understand the dynamics of fiduciary execution. Findings indicate that prior to the Constitutional Court ruling, creditors could directly execute guarantees without judicial intervention. However, post-ruling, the execution process must adhere to more stringent and formal legal procedures, ensuring protection of debtor rights and preventing arbitrary actions. This reform aims to ensure that fiduciary execution is conducted fairly, providing legal certainty for all parties involved.